LGG-09. A Nationwide Service Evaluation of Safety, Radiologic and Visual Outcome Refining Bevacizumab-based Treatments in Children with Progressive Low-Grade Glioma. (3rd June 2022) - Green, Katherine; Panagopoulou, Paraskevi; D'Arco, Felice; O'Hare, Patricia; Bowman, Richard; Walters, Bronwen; Dahl, Christine; Jorgensen, Mette; Patel, Pritesh; Slater, Olga; Ahmed, Rehana; Bailey, Simon; et al.
Abstract: INTRODUCTION : Bevacizumab/Irinotecan is currently 3rd-line treatment in the UK for progressive Paediatric Low-Grade Glioma (PLGG) based on limited evidence. A nationwide service evaluation was conducted to review its safety and efficacy amongst a larger cohort. METHODS : Data from children with PLGG receiving Bevacizumab-based Treatments (BBT) from 11 UK Centres (2009-2020) were reviewed. Radiological and visual outcomes were based on standardized measurements. Clinical-radiological correlation was investigated. Time to progression from BBT stop, progression free-survival (PFS) curves and multivariate analysis of prognostic factors (p 0.05) were performed. RESULTS : 88 children with PLGG (88% OPG, 24% NF1) had BBT for radiological (43%), visual (20%) or combined (27%) progression, after 40 months (median) from diagnosis. Amongst OPG cases, visual acuity (VA) per eye (better/worse) before BBT was logMAR 0.0-0.3 (23/7) 0.3 - 1.0 (27/20), > 1.0 (14/18) and LP/NLP (8/27), with 19/8 children respectively blind (LP/NLP) in one or both eyes. Bevacizumab 10 mg/kg every 14 days (median 24 doses) was given as 3rd line+ with Irinotecan (85%) or alongside 1st/2nd line chemo (15%) leading to remarkable radiological (88%) and visual (74%) responses (stable or improved) within 3-6 months, with limited toxicity. 12% progressed on treatment, and 8% died unrelated to BBT. After initial response 65% progressed at a median of 8 months (4 - 23) after BBT, resulting in 3-year-all-causes-PFS of 16% and 3-yr-visual-PFS of 45% from start of BBT. Visual concordance with MRI was poor (36%) but increases (47%) when better-eye determines visual outcome. Lack of NF1 and diencephalic syndrome (DS) at presentation were independent negative prognostic factors for PFS. CONCLUSIONS : A remarkable but transient effect of BBT has been confirmed. Visual > radiological responses can be sustained after BBT. Variations in current BBT strategies justifies further research, including the potential upfront use alongside conventional first-line chemotherapy as sight-saving strategy.